Carcinosarcoma of The Esophagus: a Rare Neoplasm - Case Report ans Literature Review - Felizola, Saulo José Alves (2008)
Carcinosarcoma of the esophagus is a rare type of neoplasm, described for the first time by Virchow in 1865. Total or partial esophagectomy is the standard treatment. There is limited experience concerning the benefits of radiotherapy or chemotherapy as adjuvant treatment. About 60% of patients submitted to esophagectomy are alive at three years after surgery. The authors discuss the case of a 52-year-old male with progressive solid food dysphagia and 9Kg weight loss in 2 months. Endoscopy and tumor biopsy showed an invasive, poorly differentiated carcinoma, based on which a total esophagectomy was performed. Final histopathological diagnosis was grade III polypoid carcinosarcoma. After a multidisciplinary review, the medical team opted to maintain the patient under observation with no further intervention scheduled. The patient is now clinically well after 23 months of follow-up.